High Capacity Lithium Ion Battery Anodes Using Sn Nanowires Encapsulated Al2O3 Tubes in Carbon Matrix. Issue 5 (5th January 2016) - Fang, Dong; Li, Licheng; Xu, Weilin; Zheng, Hongxing; Xu, Jie; Jiang, Ming; Liu, Ruina; Jiang, Xiaosong; Luo, Zhiping; Xiong, Chuanxi; Wang, Qing
Abstract : Tin (Sn) is one of the promising anode candidates for next generation applications in lithium ion batteries with high energy densities, but it suffers from drastic volume change (about 260%) upon lithiation. To address this issue, herein an efficient method is reported for coating Sn nanowires with an amorphous Al2 O3 layer (Sn‐Al2 O3 ) based on a combination of mechanical pressure injection technique and partial dissolution of the anodic aluminum oxide template. Further, the Sn nanowires coated with Al2 O3 are dispersed into carbon matrix (Sn‐Al2 O3 ‐C) by ball milling. In this structure, Al2 O3 helps to maintain structural integrity during charge–discharge process, and the introduced carbon matrix enhances electronic conductivity of the overall electrode. As a result, the Sn‐Al2 O3 ‐C nanocomposite exhibits an enhanced cyclic and rate performance, namely, retaining the capacities of 1308.8 mAh g −1 at the current density of 30 mA g −1 after 20 cycles, 1063.3 mAh g −1 at the current density of 200 mA g −1, and 834.2 mAh g −1 at the current density of 500 mA g −1 after 100 cycles. Abstract : Sn‐based electrodes exhibit a huge volume change during the insertion and extraction of lithium ions. Here, an effective method for coating the Sn nanowires with an amorphous Al2 O3 layer is presented (Sn‐Al2 O3 nanowires). Further, the nanowires are dispersed in a carbon matrix (Sn‐Al2 O3 ‐C), which has a high reversible capacity and good rate capability for lithium batteries.